ALLOMORPHIC AND ISOMORPHIC FEATURES OF COGNITIVE SYNONYMS IN ENGLISH AND UZBEK LANGUAGES - Mahliyo Madiyarova Vaxid qizi (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Annotation: This article explores the cognitive synonyms in English and Uzbek, focusing  on  their  allomorphic  and  isomorphic  features.  Isomorphic  characteristics highlight shared semantic similarities and contextual applications, emphasizing how both languages utilize synonyms to enrich expression. In contrast, allomorphic features reveal  cultural  connotations,  morphological  differences,  and  idiomatic  expressions unique to each language.